Clinical phenotype and trio whole exome sequencing data from a patient with glycogen storage disease IV in Indonesia(NCBI) - Ivan William Harsono; Yulia Ariani; Beben Benyamin; Fadilah Fadilah; Dwi Ari Pujianto; Cut Nurul Hafifah; Titis Prawitasari (Data in Brief)
Glycogen storage disease type IV (GSD IV) is a rare disease caused by a defect in glycogen branching enzyme 1 (GBE1), which played a crucial role in glycogen branching. GSD IV occurs once in approximately 1 in every 760,000 to 960,000 live births and is inherited in an autosomal recessive pattern. Early diagnosis of GSD IV is challenging due to non-specific symptoms, such as liver and spleen enlargement, which can overlap with other hematologic and hepatobiliary disorders. The non-specific clinical finding (phenotype) and identification of novel mutation adds the complexity of diagnosing and confirming rare disease. This often results in delayed diagnosis, typically 5.6 to 7.6 years later, with only 50% of cases being diagnosed, while the remaining cases are classified as undiagnosed rare diseases due to either the absence of identifiable potential variants or the presence of novel variants requiring further functional studies to confirm their pathogenicity. Proband and trio whole exome sequencing analysis remains a cost-effective and widely available method for diagnosing rare diseases detecting between 21 and 40% of cases. We present a trio (familial) exome sequences data from a patient with Glycogen Storage Disease IV from Indonesia. The clean and adapter trimmed FASTQ files of these sequences are available under BioProject accession number PRJNA1077459 with Sequence Read Archive accession numbers SRR27997290-SRR27997292.